Sedimentology of plio-pleistocene gravel barrier deposits in the palaeo-Orange River mouth, Namibia : depositional history and diamond mineralisation - Spaggiari, Renato Igino (Rhodes University, Faculty of Science, Department of Geology, 2011)
The largest known marine diamond placer, the Namibian mega-placer, lies along the Atlantic coast of south-western Africa from the Orange River mouth 1,000 km northwards to the Namibian-Angolan border. The most economically viable portion of the Namibian mega-placer (>75 million carats recovered at >95% gem quality) comprises onshore and offshore marine deposits that are developed within ∼100km of the Orange River outfall. For much of the Cainozoic, this long-lived fluvial system has been the main conduit transporting diamonds from kimberlitic and secondary sources in the cratonic hinterland of southern Africa to the Atlantic shelf that has been neutrally buoyant over this period. Highly energetic marine processes, driven in part, by southerly winds with an attendant northward-directed longshore drift, have generated terminal placers that are preserved both onshore and offshore. This study, through detailed field sedimentological and diamond analyses, investigates the development and mineralisation of gravel barrier deposits within the ancestral Orange River mouth area during a major ∼30 m regional transgression ('30 m Package') in the Late Pliocene. At that time, diamond supply from this fluvial conduit was minimal, yet the corresponding onshore marine deposits to the north of the Orange River mouth were significantly diamond enriched, enabling large-scale alluvial diamond mining to take place for over 75 years. Of the entire coastline of south-western Africa, the most complete accumulation of the '30 m Package' is preserved within the palaeo-Orange River mouth as barrier spit and barrier beach deposits. Arranged vertically and laterally in a 16m thick succession, these are deposits of: (1) intertidal beach, (2) lagoon and washover, (3) tidal inlet and spit recurve and (4) storm-dominated subtidal settings. These were parts of larger barrier features, the bulk of which are preserved as highstand deposits that are diamond-bearing with varying, but generally low grades (<13 stones (diamonds) per hundred tons, spht). Intertidal beach and spit recurve deposits have higher economic grades (12-13 spht) due to the energetic sieving and mobile trapping mechanisms associated with their emplacement. In contrast, the less reworked and more sandy subtidal, tidal inlet and washover deposits have un-economic grades (<2 spht). Despite these low grades, the barrier deposits have the largest average stone (diamond) size (1-2 carats/stone, cts/stn) of the entire Namibian mega-placer, given their proximity to the ancestral Orange River outfall. This study demonstrates that barrier shoreline evolution at the fluvial/marine interface was controlled by: (1) a strong and coarse fluvial sediment supply that sustained shoreline growth on a highly energetic coast, (2) accommodation space facilitating sediment preservation and (3) short-duration, high-frequency sea-level cycles superimposed on the∼30 m regional transgression, promoting hierarchal stacking of progradational deposits. During these sea-level fluctuations, diamonds were 'farmed' from older, shelf sequences in the offshore and driven landward to accumulate in '30 m Package' highstand barrier deposits. In spite of the large supply of diamonds, their retention in these deposits was poor due to an incompetent footwall of ancestral Orange River mouth sediment and the inherent cobble-boulder size of the barrier gravels. Thus the principal process controlling diamond entrapment in these barrier deposits was kinetic sieving in a coarse-grained framework. Consequently, at the marine/fluvial interface and down-drift for ∼5 km, larger diamonds (1-2 cts/stn) were retained in low-grade (<2 spht), coarse-gravel barrier shorelines. Smaller diamonds (mostly < I cts/stn) were rejected into the northward-driven littoral sediments and further size-sorted along ∼95 km of Namibian coast to accumulate in finer, high-grade beach placers (> 100 spht) where bedrock footwall promoted such high concentrations. The gravel-dominated palaeo-Orange River mouth is considered to be the ' heart' of the Namibian mega-placer, controlling sediment and diamond supply to the littoral zone further north. Although coarse gravel is retained at the river mouth, the incompetence of this highly energetic setting to trap diamonds renders it sub-economic. This ineffectiveness at the fluvial/marine interface is thus fundamental in enriching the coastal tract farther down-drift and developing highly economic coastal placers along the Atlantic coast of south-western Africa.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Diamond mines and mining -- Namibia; Sediments (Geology) -- Orange River Estuary (Namibia and South Africa); Diamond deposits -- Orange River Estuary (Namibia and South Africa)